Rational dispensing of oral dosage forms of medicines to children at a teaching hospital in Sri Lanka - Abarna Nadeshkumar; Gitanjali Sathiadas; Shalini Sri Ranganathan (BMC, 2020)
Abstract Background Good dispensing practice is vital for rational use of medicines. There are many paediatric specific challenges when maintaining good dispensing practices to children. Lack of age appropriate dosage forms, lack of medicines in strengths suitable for children, lack of palatable medicines, lack of expertise in paediatric pharmacy are few challenges faced when maintaining good dispensing practices to children. These challenges contribute to poor dispensing practices. Hence there is an urgent need to investigate whether oral dosage forms of medicines are dispensed rationally to children. The objective of this study was to describe the rational dispensing practice of oral dosage forms of medicines to children in a Teaching Hospital in Sri Lanka. Methods A descriptive cross sectional study was conducted to assess the dispensing practice of 1800 oral dosage forms of medicines dispensed to children under the age of 12 years in two outdoor pharmacies over a period of 1 year using validated indicators. Required data were extracted from the prescriptions and by observation using a structured pre-tested observation sheet. Descriptive statistics and wherever relevant, chi square test were used in analysing the data. Results Information on 1800 oral dosage forms was obtained from 1889 medicines dispensed to 727 children. Liquids were 52% [95% CI: 50-55%] of these oral dosage forms. Of the solid dosage forms, about one quarter required manipulation prior to administration such as splitting and dissolving or crushing the adult dosage form. None of the medicine packs or bottles had the patient name on the label. Conclusion Dispensing practice of oral dosage forms of medicines to children has room for improvement.